FLIM as a Promising Tool for Cancer Diagnosis and Treatment Monitoring - Ouyang, Yuzhen; Liu, Yanping; Wang, Zhiming M.; Liu, Zongwen; Wu, Minghua (Nano-Micro Letters, 2021)
Fluorescence lifetime imaging microscopy (FLIM) has been rapidly developed over the past 30 years and widely applied in biomedical engineering. Recent progress in fluorophore-dyed probe design has widened the application prospects of fluorescence. Because fluorescence lifetime is sensitive to microenvironments and molecule alterations, FLIM is promising for the detection of pathological conditions. Current cancer-related FLIM applications can be divided into three main categories: (i) FLIM with autofluorescence molecules in or out of a cell, especially with reduced form of nicotinamide adenine dinucleotide, and flavin adenine dinucleotide for cellular metabolism research; (ii) FLIM with Förster resonance energy transfer for monitoring protein interactions; and (iii) FLIM with fluorophore-dyed probes for specific aberration detection. Advancements in nanomaterial production and efficient calculation systems, as well as novel cancer biomarker discoveries, have promoted FLIM optimization, offering more opportunities for medical research and applications to cancer diagnosis and treatment monitoring. This review summarizes cutting-edge researches from 2015 to 2020 on cancer-related FLIM applications and the potential of FLIM for future cancer diagnosis methods and anti-cancer therapy development. We also highlight current challenges and provide perspectives for further investigation. Highlights: 1 Fluorescence lifetime imaging microscopy (FLIM) applications for cancer diagnosis and treatment monitoring combined with reduced form of nicotinamide adenine dinucleotide, Förster resonance energy transfer (FRET), and biosensors are reviewed. 2 Principles of FLIM, previous clinical applications, and development history are introduced. 3 The current challenges and prospects for the potential of FLIM for cancer diagnosis and promotion of the effect of anti-cancer treatment are discussed.